2011
DOI: 10.1073/pnas.1109625108
|View full text |Cite
|
Sign up to set email alerts
|

Dysbindin-1 mutant mice implicate reduced fast-phasic inhibition as a final common disease mechanism in schizophrenia

Abstract: DTNBP1 (dystrobrevin binding protein 1) is a leading candidate susceptibility gene in schizophrenia and is associated with working memory capacity in normal subjects. In schizophrenia, the encoded protein dystrobrevin-binding protein 1 (dysbindin-1) is often reduced in excitatory cortical limbic synapses. We found that reduced dysbindin-1 in mice yielded deficits in auditory-evoked response adaptation, prepulse inhibition of startle, and evoked γ-activity, similar to patterns in schizophrenia. In contrast to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 85 publications
6
88
1
Order By: Relevance
“…Cortical PV + interneuron pathology, particularly in the hippocampus, is a frequent feature of rodent models of schizophrenia pathogenesis and may be an outcome common to multiple susceptibility pathways in this disorder (6,7,12,28). The current study examines the impact of the loss of a major regulator of cortical PV + interneuron progenitor proliferation.…”
Section: Drug Groups Combined) (D) Average Post-amph Locomotion Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical PV + interneuron pathology, particularly in the hippocampus, is a frequent feature of rodent models of schizophrenia pathogenesis and may be an outcome common to multiple susceptibility pathways in this disorder (6,7,12,28). The current study examines the impact of the loss of a major regulator of cortical PV + interneuron progenitor proliferation.…”
Section: Drug Groups Combined) (D) Average Post-amph Locomotion Ismentioning
confidence: 99%
“…Although we expect these abnormalities to have effects on cognition and behavior, we and others have observed no evidence for qualitative sensory or motor (including cerebellar) phenotypes that would confound psychomotor or cognitive assessments used in this study. Notably, in schizophrenia, and in several rodent models of genetic susceptibility, hippocampal interneuron deficits occur in the context of cerebral cortical thinning, cerebellar pathology, and cell metabolic abnormalities (6,28,29,(33)(34)(35). dependent cognition assessed using the fear conditioning paradigm described for Fig.…”
Section: Drug Groups Combined) (D) Average Post-amph Locomotion Ismentioning
confidence: 99%
“…From these studies, we have learned the key roles played by schizophrenia risk gene products such as TrkB, ErbB4, (receptors for brain-derived neurotrophic factor and neuregulin, respectively), dysbindin, and cannabinoid receptor 1 in the maturation process of PV + neurons (30,36,63,239,253). Interestingly, it was recently shown that deletion of selenoprotein expression or of the Se-dependent glutathione peroxidase 4 severely affects the maturation of PV + neurons (245).…”
Section: Nox2 In Schizophreniamentioning
confidence: 99%
“…[36][37][38] Ultimately, interneuron dysfunction could contribute to altered sensory perception, 39 deficits in working memory, 18,40 attention, 41 and learning. 42 Recent studies have revealed anomalies in hippocampal and/or prefrontal PVI in many preclinical animal models aiming to reproduce genetic vulnerabilities [43][44][45][46] or environmental risk factors 47 such as prenatal maternal stress, 48 maternal and perinatal immune challenge, 49,50 hypoxia, 51,52 early-life iron deficiency, 53 maternal separation, 54 and social isolation. 55,56 Similarly, nongenetic developmental models also result in altered prefrontal PVI.…”
Section: Pvi/pnn Impairmentmentioning
confidence: 99%